Genome-Wide Identification and Analysis of the Polycomb Group Family in Medicago truncatula - Zhao, Yuanyuan (Int J Mol Sci, 2021)
Polycomb group (PcG) proteins, which are important epigenetic regulators, play essential roles in the regulatory networks involved in plant growth, development, and environmental stress responses. Currently, as far as we know, no comprehensive and systematic study has been carried out on the PcG family in Medicago truncatula. In the present study, we identified 64 PcG genes with distinct gene structures from the M. truncatula genome. All of the PcG genes were distributed unevenly over eight chromosomes, of which 26 genes underwent gene duplication. The prediction of protein interaction network indicated that 34 M. truncatula PcG proteins exhibited protein–protein interactions, and MtMSI1;4 and MtVRN2 had the largest number of protein–protein interactions. Based on phylogenetic analysis, we divided 375 PcG proteins from 27 species into three groups and nine subgroups. Group I and Group III were composed of five components from the PRC1 complex, and Group II was composed of four components from the PRC2 complex. Additionally, we found that seven PcG proteins in M. truncatula were closely related to the corresponding proteins of Cicer arietinum. Syntenic analysis revealed that PcG proteins had evolved more conservatively in dicots than in monocots. M. truncatula had the most collinearity relationships with Glycine max (36 genes), while collinearity with three monocots was rare (eight genes). The analysis of various types of expression data suggested that PcG genes were involved in the regulation and response process of M. truncatula in multiple developmental stages, in different tissues, and for various environmental stimuli. Meanwhile, many differentially expressed genes (DEGs) were identified in the RNA-seq data, which had potential research value in further studies on gene function verification. These findings provide novel and detailed information on the M. truncatula PcG family, and in the future it would be helpful to carry out related research on the PcG family in other legumes.